Implementasi E-Budgeting dalam Pengelolaan APBD Kota Surabaya dalam rangka Meningkatkan Transparansi Keuangan Daerah - Azzahratullah, Rizky Amelia; Azka, Amalia; Fanida, Eva Hany (FIA Unkris Press, 2026)
This study is motivated by the problem of low transparency and the high risk of manipulation in regional budget management, which drives the need for digital transformation in public governance. The City of Surabaya, as a pioneer in implementing an electronic budgeting system, is used as the object of analysis to assess the extent to which the system enhances openness, accountability, and efficiency in public financial management. The study aims to examine the effectiveness of this system in supporting clean governance and strengthening public trust. The research employs a qualitative approach with a descriptive analytical method, utilizing secondary data such as policy documents, financial reports, and observations of the digital system used by the local government. The analysis process involves identifying the relationship between system features and transparency indicators, followed by a systematic evaluation of implementation to assess the alignment between planning and actual practice. The findings indicate that the electronic budgeting system strengthens internal control through system locking mechanisms, standardized pricing, and digitally traceable activity records. In addition, open access to information enables public oversight, thereby enhancing government accountability. However, challenges remain, particularly in terms of limited human resource capacity and gaps in digital literacy that may hinder implementation effectiveness. Therefore, strengthening capacity and adopting inclusive strategies are essential to ensure the sustainability and equitable benefits of the system.